HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN DIARE PADA ANAK USIA 12-24 BULAN DI PUSKESMAS TERJUN KECAMATAN MEDAN MARELAN TAHUN 2014 - henny oktaviani siregar; Rahayu Lubis; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Diarrhea is a global problem with the high rates of morbidity and mortality in children in the world. To achieve optimal growth and protect infant from disease like diarrhea mother should give an exclusive breastfeeding to the infant.The purpose of this research was to determine the associated between exclusive breastfeeding with the incidence of diarrheain children aged 12-24 months at Puskesmas Terjun, Medan Marelan in 2014. Method of research conducted is cross sectional analytic approach.,This sample is 105 children aged 12-24 months.The independent variable is the Exclusive Breastfeeding and the dependent variable is the incidence of diarrhea. The sampling technique used in this study was accidental sampling. The research instrument was a questionnaire. Analysis of data through two stages, univariate data were analyzed descriptively and bivarate data were analyzedusing chi square test with 95% confidence interval (CI). The study results were obtained proportion of diarrhea in Puskesmas Terjun is as much as 61%. The highest proportion of children who have a mother with age <35 years old is 63,8%, a high education level (65,7%), not working mothers (51,4%), low knowledge (76,2%), children <18 months (54,3%), male gender (55,2%), PMT (supplementary feeding) ≤6 months (73,3%), complete immunization (81,9%), and not exclusive breastfeeding (73,3%). Bivariate results indicate a significant association between maternal education level (p = 0,003), occupation (p = 0,001) level of knowledge (p = 0,014), PMT (p = 0,001), the completeness of immunization (p = 0,022) and breastfeeding exclusive (p = 0,001) with the incidence of diarrhea. It is recommended to mothers in Puskesmas Terjun, Medan Marelan to give the infants exclusive breastfeeding until 6 months old to reduce morbidity and mortality due to diarrhea. Keywords: Characteristics,Exclusive breastfeeding, Diarrhea